Novel cloning method for recombinant adenovirus construction in Escherichia coli - Souza, D W (BioTechniques, 1999)
pAd(vantage) is a rapid cloning system for generating recombinant adenoviruses. The system is based on manipulating the full-length adenovirus genome as a stable plasmid in E. coli using intron-encoded endonucleases. These intron-encoded endonucleases cut their recognition sequences, which range from 15-39 bp, with high specificity. Their unusual long homing sequence makes them rare-cutting and ideal for use as cloning sites. We report how transgenes can easily be cloned directly into the E1 region of an adenoviral plasmid, followed by transfection into a mammalian packaging cell line, to produce homogeneous recombinant viruses without the need for plaque purification